Treatment of pure aortic regurgitation using surgical or transcatheter aortic valve replacement between 2018 and 2020 in Germany - Oettinger, Vera; Hilgendorf, Ingo; Wolf, Dennis; Stachon, Peter; Heidenreich, Adrian; Zehender, Manfred; Westermann, Dirk; Kaier, Klaus; von zur Mühlen, Constantin (Frontiers in Cardiovascular Medicine, 2023)
Background In pure aortic regurgitation, transcatheter aortic valve replacement (TAVR) is not yet used on a regular base. Due to constant development of TAVR, it is necessary to analyze current data. Methods By use of health records, we analyzed all isolated TAVR or surgical aortic valve replacements (SAVR) for pure aortic regurgitation between 2018 and 2020 in Germany. Results 4,861 procedures—4,025 SAVR and 836 TAVR—for aortic regurgitation were identified. Patients treated with TAVR were older, showed a higher logistic EuroSCORE, and had more pre-existing diseases. While results indicate a slightly higher unadjusted in-hospital mortality for transapical TAVR (6.00%) vs. SAVR (5.71%), transfemoral TAVR showed better outcomes, with self-expanding compared to balloon-expandable transfemoral TAVR having significantly lower in-hospital mortality (2.41% vs. 5.17%; p = 0.039). After risk adjustment, balloon-expandable as well as self-expanding transfemoral TAVR were associated with a significantly lower mortality vs. SAVR (balloon-expandable: risk adjusted OR = 0.50 [95% CI 0.27; 0.94], p = 0.031; self-expanding: OR = 0.20 [0.10; 0.41], p < 0.001). Furthermore, the observed in-hospital outcomes of stroke, major bleeding, delirium, and mechanical ventilation >48 h were significantly in favor of TAVR. In addition, TAVR showed a significantly shorter length of hospital stay compared to SAVR (transapical: risk adjusted Coefficient = −4.75d [−7.05d; −2.46d], p < 0.001; balloon-expandable: Coefficient = −6.88d [−9.06d; −4.69d], p < 0.001; self-expanding: Coefficient = −7.22 [−8.95; −5.49], p < 0.001). Conclusions TAVR is a viable alternative to SAVR in the treatment of pure aortic regurgitation for selected patients, showing overall low in-hospital mortality and complication rates, especially with regard to self-expanding transfemoral TAVR.